2018
DOI: 10.1007/s11356-018-2516-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental genotoxicity and risk assessment in the Gulf of Riga (Baltic Sea) using fish, bivalves, and crustaceans

Abstract: Environmental genotoxicity in the Gulf of Riga was assessed using different bioindicators (fish, clams, and isopods) collected from 14 study stations. Comparison of genotoxicity responses (micronuclei (MN) and nuclear buds (NB)) in blood erythrocytes of herring (Clupea harengus), eelpout (Zoarces viviparous), and flounder (Platichthys flesus) revealed the species- and site-specific differences. For the first time, the analysis of genotoxicity was carried out in gill cells of isopods Saduria entomon. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Labeo rohita was the most sensitive species. Micronuclei are formed at different periods of the cell cycle during cell division, after attack by environmental toxicants (Bolognesi and Hayashi 2011; Butrimavičienė et al 2018). The micronucleus test was originally developed for mammalian species but has now been widely used in fish (Ahmed et al 2011; Bolognesi and Hayashi 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Labeo rohita was the most sensitive species. Micronuclei are formed at different periods of the cell cycle during cell division, after attack by environmental toxicants (Bolognesi and Hayashi 2011; Butrimavičienė et al 2018). The micronucleus test was originally developed for mammalian species but has now been widely used in fish (Ahmed et al 2011; Bolognesi and Hayashi 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate knowledge by dairy industry organizations and treatment plants on wastewater characteristics and its effect on the municipal wastewater system and receiving water bodies (Gulf of Riga) leads to damage to the environment. Studies revealed the potential sediment toxicity in Gulf of Riga by using acute toxicity bioassay (survival test) for many aquatic lives (Strode et al ., 2017; Butrimavičienė et al ., 2018). The presence of unmeasured contaminants discharged from municipal water treatment plants could be responsible for toxicity to aquatic animals in Gulf of Riga sediments, which may be detrimental to human health.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its irreparable nature, the increase in micronuclei is considered a relevant toxicological endpoint. 26,27 The aim of the present study was to pursue nonmutagenic derivatives of emodin that can also be applied to textiles using waterless dyeing methods. Specifically, our group modified the emodin structure by incorporation of one or two acryloyl groups according to the chemistry shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The micronucleus test consists of a relatively quick and simple technique for assessing chromosomal damage. Because of its irreparable nature, the increase in micronuclei is considered a relevant toxicological endpoint 26,27 …”
Section: Introductionmentioning
confidence: 99%